KOMPOSISI BERBAGAI MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN PORANG (Amorphophallus onchophyllus) - Harsani, Harsani; Rachmat, Rachmat; Syaifuddin, Syaifuddin; Hamzah, Pratiwi; Nurjusiah, Nurjusiah (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2024)
T The selection of the right growing medium is a crucial factor in the cultivation of porang (Amorphophallus onchophyllus). The growing medium's quality directly affects this plant's growth and yield. This study aims to find out the effect of the composition of various planting media on the growth of porang plants with the observed parameters consisting of bud growth time, the number of shoots, shoot height, and root volume. This study employed a Randomized Block Design with 4 treatments and 3 replications. The treatments given were P0 (without treatment), P1 (2,000 g of soil + 1,000 g of goat manure + 1,000 g of husk charcoal), P2 (2,000 g of soil + 1,000 g of goat manure + 1,000 g of banana midrib), and P3 (2,000 g of soil + 1,000 g of goat manure + 1,000 g bamboo leaf charcoal). This study was followed by extension activities which were evaluated at the beginning (the initial evaluation) and the end (the final evaluation). Results indicated that the use of various compositions of effective growing media had a significant effect on the outcomes. The planting media composition on P2 with 2,000 g of soil, 1,000 g of goat manure, and 1,000 g of banana midrib gave the best results for all parameters in which the average shoot growth time was 5 DAP, the average number of shoots was 5 and 6 shoots after 60 DAP, the average shoot height was 2.9 cm at 60 DAP, and the average root volume was 19.9 ml.